Expression and Humoral Response of A-Kinase Anchor Protein 4 in Cervical Cancer. Issue 4 (1st May 2013) - Agarwal, Sumit; Saini, Shikha; Parashar, Deepak; Verma, Archana; Jagadish, Nirmala; Batra, Aruna; Suri, Sushma; Bhatnagar, Amar; Gupta, Anju; Ansari, Abdul S.; Lohiya, Nirmal K.; Suri, Anil
Abstract : Background: Cervical cancer is one of the major gynecologic cancers. In developing countries, because of a lack of medical support and infrastructure, cervical cancer is the leading cause of cancer-related deaths. Therefore, there is a need to identify novel biomarkers for cervical cancers. In this context, cancer-testis (CT) antigens represent a unique class of tumor antigens that have been shown to be associated with various solid tumors. These antigens have restricted expression in testis and no expression in somatic tissues. Because of their restricted expression, CT antigens are novel candidate molecules for early detection and diagnosis and immunotherapy. In the present study, novel CT antigen A-kinase anchor protein 4 (AKAP4) expression and humoral response were investigated in patients with cervical cancer. Methods: In this study, 74 cervical cancer tissue specimens, which included different tumor stages (stage I [n = 35], stage II [n = 39]) and histologic grades (grade 1 [n = 17], grade 2 [n = 46], and grade 3[n = 11]) and 62 adjacent noncancerous tissue specimens were investigated for AKAP4 gene expression by using reverse transcriptase polymerase chain reaction and in situ RNA hybridization. Furthermore, AKAP4 protein expression was determined by immunohistochemistry. In addition, humoral response against purified recombinant AKAP4 protein was determined in available sera of 70 patients with cervical cancer by enzyme-linked immuno assay (ELISA). Findings: Our study revealed that AKAP4 gene and protein expression was detected in 86% of total patients with cervical cancer. Based on the AKAP4 immunoreactivity score, most of stage I (n = 22/29) and stage II (n = 30/35) specimens revealed high AKAP4 expression (≥50% AKAP4-positive cells). A-kinase anchor protein 4 expression was significantly associated with early grades tumor specimens ( P = 0.023). In addition, humoral response was detected in 53% of patients irrespective of stages, lymph node positivity, and grades. Conclusions: Collectively, our data indicate the putative role of AKAP4 in early tumorigenesis and may be implicated as a biomarker and immunotherapeutic target for cervical cancer.